The COVID-19 Pandemic’s Disruptions to Preschool Children’s Cognitive, Social-Emotional, and Executive Functioning Skills - Vi-Nhuan Le; Diana Schaack; Cristal Cisneros; Jolene Gregory (AERA Open)
Using a longitudinal design that analyzed data captured before and after pandemic-related preschool closures, we compared the kindergarten readiness of children whose preschool experiences were interrupted by the pandemic with the kindergarten readiness of prepandemic children whose preschool experiences were more typical. Pandemic-related disadvantages were observed for early math, social-emotional, and executive functioning, with the pandemic-affected cohort showing disadvantages of between 11 and 18 percentage points. Developmental disadvantages were observed across all income levels, and there was suggestive evidence that the loss of preschool affected the social-emotional and executive functioning skills of children from lower- and higher-income groups differently, although these differences were not always statistically significant. Policy implications are discussed.